Managing the Immigration and Employment of Non-EU Nationals in Ireland - Ruhs, Martin (Trinity College Dublin, 2005)
Ireland's recent transformation into a country of immigration has raised new and important policy issues. Rapid economic growth and relatively liberal policies toward the admission of migrant workers have resulted in a significant increase in the number of non-Irish workers coming to Ireland since the late 1990s particularly from outside the pre-enlarged European Union. Little is known about the impacts of these recent migration flows to Ireland. This has left policy-makers in the difficult position of having to design policies based on an incomplete and contested evidence base. Public debates and policies have been further hampered by a lack of discussion about the desirable objectives of Ireland's labour immigration policies.Managing the Immigration and Employment of non-EU Nationals in Ireland addresses four key questions in the debate and design of Ireland's labour immigration policies: What have been the labour immigration flows and policies in Ireland? What are the consequences of international labour migration to Ireland? What should be the principles and objectives of Ireland's labour immigration policy? What policies are best suited to achieve these objectives?In addition to identifying the current gaps in the evidence and discussion on labour migration, this paper suggests a set of basic policy principles that could be adopted to improve the process of debating and designing labour immigration policy in Ireland. It also discusses the need and specific policy options for: re-adjusting Ireland's work permit system; introducing a permanent immigration programme; and combating the illegal employment of migrant workers.
Keywords: Social Policy; Immigration; Ireland